The chemical constituents of citrus fruit peel essential oil - 465729 Cheo, Yee How; Muhammad Sum Idris; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2007